Efeito da hidralazina na sobrevida, na resposta inflamatória e no estresse oxidativo em modelo animal de sepse - Santos, Danillo Menezes dos (2021)
Sepsis is characterized by an amplified systemic immunoinflammatory response produced by a microorganism. Its pathophysiological mechanism is complex and involves the activation of inflammatory cytokine signaling pathways and oxidative stress. Due to the high mortality in ICU patients, the scientific community has been constantly looking for safe and effective therapies for the treatment of sepsis. And in this context, hydralazine (HDZ) is a strong candidate. Although HDZ is best known as a potent vasodilating substance and has been used frequently in the past five decades as an antihypertensive, due to its safety and low risk of causing toxicity, studies have shown that it also has potent antioxidant properties, especially in inhibition of ROS and RNS formation and sequestration in vivo and in vitro. Thus, the main objective of this study was to evaluate the ability of hydralazine (HDZ) to mitigate mortality, the inflammatory response and oxidative stress induced by sepsis, and to investigate its possible mechanisms of action. Sepsis was induced by the ligation and cecal perforation (CLP) method in male Wistar rats. After surgery, the animals were randomly divided into three groups: sham, sepsis and sepsis + HDZ (1 mg/kg, s.c; 4 h after sepsis induction and after 12-12 hours until 48 h). All groups were monitored for 48 h to assess survival rate, clinical, biochemical and cellular parameters. After euthanasia, blood, spleen, liver and kidneys were collected for analysis of markers of lipid and protein damage, serum blood cytokines, myeloperoxidase activity (MPO) and oxidative stress parameters, through the activity of catalase and superoxide dismutase enzymes. The involvement of the PI3K/Akt pathway was also investigated by western blot in the tissues of the spleen, liver and kidney. Sepsis was successfully induced by the CLP technique. HDZ administration has increased: the survival rate (from 50 to 90%); the temperature (from 33.3 ± 0.2 to 34.5 ± 0.3ºC); blood glucose concentration (from 87.6 ± 2.8 to 106.5 ± 2.1 mg/dL). HDZ treatment reduced: the clinical sepsis severity score (from 10.6 ± 0.51 to 6.5 ± 0.40 u.a.); the lactate concentration (from 36.2 ± 1.5 to 18.03 ± 1.1 mg/dL); the concentrations of cytokines TNF-α, IL-1β and IL-10 (from 10.2 ± 0.3; 99.1 ± 10.7; 1252 ± 325.3, respectively to 4.1 ± 0.4; 19 , 66 ± 4.5; 267 ± 138.1 pg/mL); MPO activity in the spleen, liver and kidney (from 26.02 ± 2.74; 0.11 ± 0.01; 0.20 ± 0.02, respectively to 13.37 ± 0.95; 0.066 ± 0.007; 0.141 ± 0.006 U / g, respectively); TBARS concentrations (from 2.33 ± 0.15; 0.92 ± 0.15; 9.14 ± 0.97 to 1.47 ± 0.07; 0.48 ± 0.06; 4.34 ± 0.36 nmol/mg protein, respectively). In addition, HDZ significantly prevented increased Akt activation in the liver and kidneys, but had no effect on the spleen. HDZ administration largely mitigated the effects of sepsis by improving inflammatory and antioxidant responses through the PI3K/Akt pathway. These findings provide strong evidence that HDZ may be a new therapeutic alternative for the treatment of sepsis.